From accreditation to quality improvement—The Danish National Quality Programme. (16th April 2021) - Uggerby, Christian; Kristensen, Solvejg; Mackenhauer, Julie; Knudsen, Søren Valgreen; Bartels, Paul; Johnsen, Søren Paaske; Mainz, Jan
Abstract: The Danish government launched a new National Quality Programme (NQP) in healthcare in 2015. It has changed the focus from old public management in terms of accreditation, regulation, rules and standards to new public governance focusing on delivering high quality healthcare and outcomes of value for the patients, health professionals and the Danish healthcare system. The NQP aims to strengthen the focus on continuous quality improvement and the launch of the programme was accompanied by a decision to phase out accreditation of public hospitals. The NQP includes 1) eight specific national quality goals, 2) a national educational programme for quality management, and 3) establishment of quality improvement collaboratives. Since the establishment of the NQP the indicator results have improved in several important clinical areas. However, causal conclusions related to the effect of the NQP cannot yet be made. This perspective on quality paper aims to give a short introduction to the NQP and documented outcomes.